Analysis of the Influence of Air Conditioning System on the Assessment Rating of Green Buiding Certification "Greenship Existing Building" - Bakhtiar Bakhtiar; Jaka Windarta; Eddy Prianto (Journal of Social Research, 2025)
This study aims to analyze the influence of the air conditioning system on achieving the Green Building certification rating for Greenship Existing Building PT Pamapersada Nusantara Head Office. The air conditioning system is a key aspect in assessing green building performance, particularly in the categories of energy efficiency, indoor air quality, and thermal comfort. The research method used was a descriptive quantitative approach with secondary data analysis in the form of energy audit documents, electricity consumption measurements, and technical data from the HVAC system installed in the building. The results show that the air conditioning system significantly contributes to points earned in the Energy Efficiency and Conservation (EEC) and Indoor Health and Comfort (IHC) categories. The implementation of an energy-efficient HVAC system, the use of high-efficiency equipment, and sound operational management can increase the efficiency of electrical energy consumption to the required limit. Indoor air quality is maintained according to standards, which positively impacts the comfort and productivity of building occupants. The results confirm that the air conditioning system is a strategic factor in achieving green building certification and serves as an important foundation for energy management and environmental sustainability efforts in existing buildings.